Psychometric Properties of the Persian Version of the Center for Epidemiological Studies Depression Scale Among the Iranian Public People During COVID-19 Pandemic - Sharif Nia, Hamid; Rahmatpour, Pardis; Sivarajan Froelicher, Erika; Pahlevan Sharif, Saeed; Kaveh, Omolhoda; Rezazadeh Fazeli, Azadeh; Sia, Chin Chin (Frontiers in Public Health, 2021)
Psychometric Properties of the Persian Version of the Center for Epidemiological Studies Depression Scale among the Iranian Public People during COVID-19 Pandemic Abstract Background: Several studies indicate a high prevalence of depression around the world during the period of COVID-19 pandemic. Using a valid instrument to capture an individual’s depression in this situation is both important and timely. The aim of present study is to evaluate the psychometric properties of the Persian version of the Center for Epidemiological Studies Depression Scale (CES-D) among the public during the COVID-19 pandemic in Iran. Method: This is a cross-sectional study that was conducted in the Iranian population (n=600) from April to July 2020. A two-part online form was used: socio-demographic characteristics and depression items (CES-D). The construct validity and internal consistency reliability of scale were evaluated. Result: The results of the exploratory factor analysis illustrated two factors with 43.35% of the total variance of the depression were explained. Confirmatory factor analysis indicated that this model fits well. Internal consistency reliability was evaluated and it was acceptable. Conclusion: The findings demonstrated that in Iranian sample this depression scale yielded two factors (somatic and positive affects) solution with suitable psychometric properties.